1993
DOI: 10.1521/soco.1993.11.2.201
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Self-Presentation: Self-Promotion in 6- to 10-Year-Old Children

Abstract: The present study explored the development of self-presentation. Subjects were eighty-five 6-, 8-, and 1 0-year-olds. Subjects were asked to tell children at another school about themselves three times: (1) a baseline self-description; (2) a self-description intended to convince the children to pick them as a partner for a game (goal-directed condition); and (3) a self-description intended to convince children who really wanted to win prizes to pick them as a partner (enhanced goal-directed condition). The sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
96
1
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 34 publications
9
96
1
4
Order By: Relevance
“…This is consistent with growing literature showing that children's appreciation of self-presentational processes undergoes significant development during primary school (Aloise-Young, 1993;Banerjee, 2002;Banerjee and Yuill, 1999;Bennett and Yeeles, 1990b). Furthermore, the present results further detail the developmental changes that children go through between 8 and 10 years of age in their thinking about modest selfpresentations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with growing literature showing that children's appreciation of self-presentational processes undergoes significant development during primary school (Aloise-Young, 1993;Banerjee, 2002;Banerjee and Yuill, 1999;Bennett and Yeeles, 1990b). Furthermore, the present results further detail the developmental changes that children go through between 8 and 10 years of age in their thinking about modest selfpresentations.…”
Section: Discussionsupporting
confidence: 92%
“…Some existing research suggests that children do consider audience information when determining how they should self-present during an interaction. In particular, children are able to change their selfpresentational tactics depending on knowledge of the audience's motivation (Aloise-Young, 1993), and children are able to change their self-presentational behaviour depending on knowledge of the audience's likes and dislikes (Banerjee, 2002). Importantly, research has also shown that children believe that different presentations of reasons for academic success and failure are appropriate for peer and adult audiences Murdock, 1993, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In our experiments recipients were not present, allowing us to specifically investigate children's motivation to appear fair to third parties, an important step forward in understanding how children develop self-presentational concerns. This approach is more analogous to research in adult impression management, which is often focused on how individuals try to influence strangers' perceptions of them (Baumeister, 1982;Leary et al, 2011), and extends investigations of self-presentation in older children in domains other than fairness (Aloise-Young, 1993;Banerjee, 2002;Hill & Pillow, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…presentation increasing as they approach eight to ten years of age (Aloise-Young, 1993;Apfelbaum, Pauker, Ambady, Sommers, & Norton, 2008;Banerjee, 2002;Piaget, 1932;Selman, 1980;Turiel, 2006). Interestingly, children become increasingly concerned with how they appear to others at the same time as they are becoming more concerned with being fair.…”
mentioning
confidence: 99%
“…This period also coincides with considerable social and emotional changes and a search for identity (Heaven, 2001). This increased uncertainty is likely to lead to heightened concern over the presentation of the self in numerous contexts (Aloiseyoung, 1993), including the physical domain (Kowalski et al, 2006). There is, however, no research that has made developmental comparisons across age groups for social physique anxiety.…”
Section: Introductionmentioning
confidence: 99%